Optimal Sizing and Placement of Renewable Energy Sources in Power System Connected Multi-Microgrids - Amel Brik; Nour EL Yakine Kouba; Ahmed Amine Ladjici (Revue des Énergies Renouvelables, 2025)
Large scale integration of distributed generation of medium and low voltage (LV) networks can be achieved by exploiting the Multi-Microgrid (MMG) concept, worldwide due to the increasing penetration of renewable energy sources. A modern technology based on the use of microgrids where DG penetration is beneficial if optimally placed. A new radial power system architecture allows the coordination between distributed generation units and Microgrids (MGs) and thus the operation of such a system in islanded mode. Different microgrid models are developed for optimal location and capacity of renewable energy RES. In this context, this paper deals with an optimal approach to find the best location and sizing capacity of DG units in a radial electrical system (RDS) using metaheuristic optimization algorithms. The objective was to minimize the total active power losses with the assurance of a good voltage profile. The application of Particle Swarm Optimization (PSO) on the IEEE 33-bus network shows the validity of the proposed algorithm to minimize power losses and incorporate optimal micro-grid in the appropriate buses, which gives the optimal capacity and location of microgrid in the distribution network.